2019
DOI: 10.1108/et-05-2018-0126
|View full text |Cite
|
Sign up to set email alerts
|

Entrepreneurial intentions: trust and network ties in online and face-to-face students

Abstract: Purpose Based on Azjen’s (1991) theory of planned behavior, the purpose of this paper is to complement the existing body of knowledge on entrepreneurial intentions (EIs) by comparing two different university environments in Spain (online and face-to-face) and their impact on EIs of university students using two components of social capital (SC), trust and network ties as variables with influence on the antecedents of EIs. Design/methodology/approach A survey was administered to online and face-to-face studen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(27 citation statements)
references
References 45 publications
3
24
0
Order By: Relevance
“…The inclusion of the network ties as a predictor of entrepreneurial intentions was confirmed and supported the findings of Pérez-Macías et al (2019) and Gelaidan and Abdulllateef (2017). On network ties, the study found that participants belonged to several social, and business networks, which helped them obtain information on business opportunities in industries of interest.…”
Section: Discussion Of Findingssupporting
confidence: 78%
See 1 more Smart Citation
“…The inclusion of the network ties as a predictor of entrepreneurial intentions was confirmed and supported the findings of Pérez-Macías et al (2019) and Gelaidan and Abdulllateef (2017). On network ties, the study found that participants belonged to several social, and business networks, which helped them obtain information on business opportunities in industries of interest.…”
Section: Discussion Of Findingssupporting
confidence: 78%
“…To address this, Sequeira et al (2007) sought to examine how network tie influences entrepreneurial intentions. Recently, Pérez-Macías et al (2019) proposed the need to extend studies with other samples on how network ties affect student's entrepreneurial intentions.…”
Section: Introductionmentioning
confidence: 99%
“…Edelman et al (2016) emphasize the dangers, especially for young, nascent entrepreneurs, of using financial resources of the family. This may have an impact on entrepreneurial intentions (Mwiya et al 2018;Pérez-Macías et al 2019). Negative effects of this strategy include relying on a convenient means of capitalization that can be demoralizing instead of capitalizing the venture by conventional means that would require more entrepreneurial efforts.…”
Section: Effect Of Family Financial Support On Entrepreneurial Successmentioning
confidence: 99%
“…Recently, research has evidenced that TPB antecedents and entrepreneurial intention for online university students are influenced by network ties (structural dimension) and shared language and vision (cognitive dimension) (Pérez-Macías et al, 2019b), and trust, reciprocity, and identification (relational dimension) in virtual communities (Pérez-Macías et al, 2018). Network ties (structural dimension) and trust (relational dimension) in virtual communities also influence TPB antecedents and entrepreneurial intention for both online and face-to-face university students (Pérez-Macías et al, 2019a).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Studies exploring the role of social capital in entrepreneurial intention, or its antecedents, have mainly focused on social capital offline (e.g., Liñán & Santos, 2007;Sequeira et al, 2007), which is developed face to face over long periods (Gedajlovic et al, 2013). Some recent studies have explored the impact of social capital in virtual communities on the entrepreneurial intention of online university students (Pérez-Macías et al, 2018, 2019b and in comparison to face-to-face students (Pérez-Macías et al, 2019a).…”
Section: Introductionmentioning
confidence: 99%